Synthesis and Structural Properties of Niobium Pentoxide Powders: A Comparative Study of the Growth Process (2016)
Powders Nb2 O5 were prepared by two different synthesis method, Sol-Gel and polymeric precursors (Pechini). In the Pechini method before adding the citric acid in the process, four different solutions were used to get the samples. For Sol-gel method, two different processes were also used in obtaining powders. The precursor was completely solubilized in ethanol and then hydrolyzed with ammonia and water. The calcination of the samples was between 500 and 750°C. The resulting powders were characterized by Scanning Electron Microscopy (SEM), Brunauer, Emmett and Teller (BET) surface area measurements, UV-visible and Raman spectroscopy. The formation of T−Nb2 O5 orthorhombic took place upon calcination at 7500C. Crystallite sizes were determined using the Scherrer method which resulted in an uniformed size of about 25 − 65nm. Ultraviolet-Visible diffuse reflectance spectroscopy indicated a variation in the optical band gap values (3.32-3.40 eV) in crystal growth process. The Raman vibrational modes indicate the presence of the orthorhombic phase of the material.